ANALISIS PERAN HUMAS PT KAI DAOP 1 JAKARTA DALAM KEGIATAN SOSIALISASI INFORMASI K3 PADA PEGAWAI - Puja Cahyaning Putri Cahyaning Putri; Ratih Siti Aminah; Tiara Puspanidra (Universitas Pakuan, 2022)
This study aims to determine the role of public relations in the socialization of K3 information to employees of PT KAI Daop 1 Jakarta. This research is descriptive research with a qualitative approach. The subjects in this study were KUPT railroad, KAUR railroad, and employees of PT KAI Daop 1 Jakarta. Data collection technique using observation, interview, and documentation. The data validity technique was determined using the source triangulation technique. The results showed that the role of public relations at PT KAI Daop 1 Jakarta as follow: (1) the role of public relations as communicator the organization and the internal and external community, namely:delivery of information on policies, activities, financial reports, appeals of disease outbreaks, achievements or achievements, as well as disaster emergency information at PT KAI Daop 1 Jakarta which is addressed to the internal and external community of the organization. (2) the role of public relations as relationship the organizations it represents is carried out in collaboration with the public and journalist’s media partners. (3) the role of public relations as back up management namely public relations carries out the activies of carrying out fact finding and communicating processes to be used as material for consideration of PT KAI Daop 1 Jakarta’s policies. (4) the role of public relations as good image maker of the organization is to provide services openly to community.